2006
DOI: 10.1088/0953-8984/18/42/010
|View full text |Cite
|
Sign up to set email alerts
|

Metastable phases and ‘metastable’ phase diagrams

Abstract: The work discusses specifics of phase transitions for metastable states of substances. The objects of condensed media physics are primarily equilibrium states of substances with metastable phases viewed as an exception, while the overwhelming majority of organic substances investigated in chemistry are metastable. It turns out that at normal pressure many of simple molecular compounds based on light elements (these include: most hydrocarbons; nitrogen oxides, hydrates, and carbides; carbon oxide (CO); alcohols… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…It turns out that there is a set of irreversible transitions to poly-CO structures corresponding to different applied pressures, which is consistent with the qualitative model suggested by Brazhkin in [4]. Starting from 7-8 GPa, some of the CO molecules are intact as in the δ crystal phase, but with different densities, and certain parts of the molecules form chains, four and five fold rings with O in the cage and carbonyl groups decorating the rings.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…It turns out that there is a set of irreversible transitions to poly-CO structures corresponding to different applied pressures, which is consistent with the qualitative model suggested by Brazhkin in [4]. Starting from 7-8 GPa, some of the CO molecules are intact as in the δ crystal phase, but with different densities, and certain parts of the molecules form chains, four and five fold rings with O in the cage and carbonyl groups decorating the rings.…”
Section: Introductionsupporting
confidence: 85%
“…We started our simulation from construction of the δ-phase of solid CO, based on experimental information from [4]. We then compressed the unit cell at the various pressures starting from 2 GPa to 18 GPa in 1 GPa increments.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, structural transitions in amorphs have been called ''phase'' transitions, even though amorph (nonequilibrium nature) and phase (equilibrium nature) are in direct contradiction. Glasses and amorphous solids are nonergodic, nonequilibrium states, and a strict physical meaning of the ''phase'' can be applied to them only conditionally (''metastable phase'') [21]. The use of terminology reserved for true equilibrium transitions (phase, latent heat, first-order nature, nucleation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic calculations of the Gibbs standard free energy and analysis of the geochemical constraints showed that the abiotic synthesis of organic compounds in hydrothermal systems is limited by the metastable equilibrium that results from kinetic barriers, which prevent the achievement of stable equilibrium [32,[35][36][37]. Most of the organic substances in condensed and dissolved phases are in a metastable state, i.e., these substances do not reach the minimum Gibbs free energy for the given composition of elements, and thus are "kinetic" or "metastable" phases [38,39].…”
Section: Methodical Approachmentioning
confidence: 99%